Pengaruh Metode Latihan Running With The Ball Terhadap Kecepatan Dribbling Futsal Pada Siswa Eksrakurikuler SMPN 12 Tambun Selatan - HR, Muh Rizqi; Kemala, Aisya (Motion: Journal Research of Physical Education, 2025)
This study aims to examine the effect of the Running With The Ball training method on increasing the dribbling speed of futsal extracurricular students at SMPN 12 Tambun Selatan. The research method used was an experiment with a one-group pretest-posttest design. The population in this study consisted of students aged 13– 15 years. Samples were taken using a sampel jenuh technique, so that 20 futsal extracurricular students at SMPN 12 Tambun Selatan were obtained as research subjects Based on the hypothesis test carried out on the independent variable (X) and the dependent variable (Y), the results of the analysis using the Test Dribbling show that the calculated t value (19,68) is greater than the t table (2,093). These results indicate that the correlation coefficient is significant, so the research hypothesis is accepted. Thus, it can be concluded that there is an Effect of the Running With The Ball Training Method on Dribbling Speed in Futsal Extracurricular Students at SMPN 12 Tambun Selatan